Sucessão do cônjuge e companheiro: uma abordagem comparativa - Moreira, Lígia Carolina Costa (2017)
With the advent of the Civil Code of 2002, the inheritance law underwent enormous modifications, especially with regard to the position of the surviving spouse among the successors of the de cujus. The purpose of this dissertation is to analyze the succession rights of the surviving spouse, the new order of hereditary vocation, their competition with the descendants and ascendants, as well as the hereditary quota that will be received in each of the situations. Faced with the lack of legislative technique and legal uncertainty introduced as provided for in Article 1.829 of the Civil Code, law students have no other choice than the difficult task of interpreting the rule, in the most correct way, thus preventing Endless controversies. In a second moment, it is verified that the Federal Constitution of 1988, in view of the social yearning, acclaimed the existence of the stable union, as a family entity protected by the State. It also analyzes the inheritance rights of the partner in competition with the descendants and ascendants of the deceased, as well as their possible competition with the surviving spouse